2007
DOI: 10.3748/wjg.v13.i3.329
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drug-induced hepatotoxicity in clinical practice: A challenge for gastroenterologists

Abstract: Currently, pharmaceutical preparations are serious contributors to liver disease; hepatotoxicity ranking as the most frequent cause for acute liver failure and postcommercialization regulatory decisions. The diagnosis of hepatotoxicity remains a difficult task because of the lack of reliable markers for use in general clinical practice. To incriminate any given drug in an episode of liver dysfunction is a step-by-step process that requires a high degree of suspicion, compatible chronology, awareness of the dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
0
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(109 citation statements)
references
References 69 publications
2
97
0
10
Order By: Relevance
“…Many currently used drugs, particularly non-steroidal anti-inflammatory drugs (NSAIDs), are implicated in liver disorders, ranging from mild aminotransferases elevation to fulminant hepatitis with a high rate of mortality [1]. While most subjects with clinically mild disease are diagnosed on an outpatient basis, patients with a more severe course require hospital admission and, in some cases, are evaluated for orthotopic liver transplantation (OLT).…”
Section: Introductionmentioning
confidence: 99%
“…Many currently used drugs, particularly non-steroidal anti-inflammatory drugs (NSAIDs), are implicated in liver disorders, ranging from mild aminotransferases elevation to fulminant hepatitis with a high rate of mortality [1]. While most subjects with clinically mild disease are diagnosed on an outpatient basis, patients with a more severe course require hospital admission and, in some cases, are evaluated for orthotopic liver transplantation (OLT).…”
Section: Introductionmentioning
confidence: 99%
“…As an essential part of adverse drug reaction (ADR), causality assessment was done using the Naranjo scale and RHUCAM score [23,24]. Naranjo scale concluded a definitive ADR with a score of 10 (> 9 is definitive) as shown in (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] We used the CIOMS/RUCAM scales to assess drug-induced liver injury and the result from the scale was "highly probably" adverse drug reaction (Scale score was 10 points). [17,18] Fonseca et al [1] reported that ALT, AST, and LDH levels were increased to more than 50 times in amiodarone-induced hepatitis because of amiodarone and that GGT and ALP levels were normal. However, there is no study in the literature on the possibility of isolated GGT elevation.…”
Section: Discussionmentioning
confidence: 99%